Multifunctional reactive MALDI matrix enabling high-lateral resolution dual polarity MS imaging and lipid C═C position-resolved MS2 imaging - Wäldchen, Fabian; Rehberg, Franziska; Wagner, Andreas H.; Heiles, Sven (Analytical chemistry, 2020)
Local lipid variations in tissues are readily revealed with mass spectrometry imaging (MSI) methods, and the resulting lipid distributions serve as bioanalytical signatures to reveal cell- or tissue-specific lipids. Comprehensive MSI lipid mapping requires measurements in both ion polarities. Additionally, structural lipid characterization is necessary to link the lipid structure to lipid function. Whereas some structural elements of lipids are readily derived from high-resolution mass spectrometry (MS) and tandem-MS (MSn), the localization of C═C double bonds (DBs) requires specialized fragmentation and/or functionalization methods. In this work, we identify a multifunctional matrix-assisted laser desorption/ionization (MALDI) matrix for spatially resolved lipidomics investigations that reacts with lipids in Paternò-Büchi (PB) reactions during laser irradiation facilitating DB-position assignment and allows dual-polarity high-resolution MALDI-MSI and MALDI MS2I studies. By screening 12 compounds for improved ionization efficiency in positive-/negative-ion mode and the functionalization yield compared to the previously introduced reactive MALDI matrix benzophenone, 2-benzoylpyridine (BzPy) is identified as the best candidate. The new matrix enables DB localization of authentic standards belonging to 12 lipid classes and helps to assign 133/58 lipid features in positive-/negative-ion mode from mouse cerebellum tissue. The analytical capabilities of BzPy as a multifunctional MALDI-MSI matrix are demonstrated by imaging endogenous and PB-functionalized lipids in mouse kidney sections with 7 μm lateral resolution in both ion modes. Tracking diagnostic lipid DB-position fragment ions in mouse pancreatic tissue with down to 10 μm pixel size allows us to identify the islets of Langerhans associated with lipid isomer upregulation and depletion.
Im Titel ist "2" in MS2 hochgestellt
Gesehen am 13.01.2021